The Students’ Integrated Personal Development In Islamic College To Face Future Careers Through Life Skill Enhancement And Faith Enlightenment Program - Aminah (El-Idarah: Jurnal Manajemen Pendidikan Islam, 2017)
In some majority Moslems country, there are found Islamic colleges which offer their curriculum to provide and enhance human resource of the students enrolling in one of the campuses. The students attending the universities absolutely prepare themselves to compete in the real life especially in workplaces. They need extra knowledge which focuses on their human resource in intellectual, emotional, and spiritual. Thus, integrated personal development is offered to overcome this problem. Life skill enhancement and faith enlightenment program is the alternative of pursuing their future challenges. Input, environment, and output (I-E-O) are urgent factors to be synergy to apply. The enhancement of life skill including professionalism in the chosen field of study, ICT mastery, English proficiency, and self -management program aims to improve their intellectual and emotional intelligences. Besides, faith enlightenment program is another thing to highlight by providing them Islamic discussion forums and spiritual advice to increase their spirituality. The program is expected to boost the youth personal development and to evoke qualified personal human resource that will be ready to face the real world especially the workforces by thinking smartly and wisely. In addition, family involvement, bureaucracy, lecturers, staffs, and friends also play the important roles in bringing those programs into reality.